Pola Pelanggaran Pemilukada dan Perluasan Keadilan Substantif - Huda, Miftakhul (Mahkamah Konstitusi Republik Indonesia, 2011)
The pattern of direct elections of regional head and the Constitutional Court practices in adjudicate disputes local elections have been developed rapidly. Some of violations color the elections of regional head. They were the mobilization and partiality of Civil Servants, abuse of office, facilities, and state budget by the incumbent candidate, and the practice of money politics. The systematic, structured as well as massive violations generally results reelected vote with a final decision or interlocutory preceded. More than that, various violations of further stages of the General Election was also assessed based on the principle of free and fair election so that the decision of the Court has eigh models based on similar characteristics.The paradigm of substantive justice made procedural rules does not open the opportunity for justice. It drives the role of the Constitutional Court put the final determinant of local democracy which is still colored by piracy and fraud. Constitutional Court justices are not only expand but also strengthen democracy that took place so as not limited to procedural democracy. With this, the examination is very extensive; the free encyclopedias assess weight and sanction violations. Paradigm has evolved to be followed by the ratio decidendi constancy previous decisions and anticipate the variety of sanctions violations by designing the right to justice itself.